Dragon's blood Croton palanostigma induces genotoxic effects in mice - Maistro, Edson Luis [UNESP]; Ganthous, Giulia [UNESP]; MacHado, Marina Da Silva; Zermiani, Tailyn; Andrade, Sérgio Faloni De; Rosa, Paulo Cesar Pires; Perazzo, Fabio Ferreira (Elsevier, 2013)
Ethnopharmacological relevance Dragon's blood is a dark-red sap produced by species from the genus Croton (Euphorbiaceae), which has been used as a famous traditional medicine since ancient times in many countries, with scarce data about its safe use in humans. In this research, we studied genotoxicity and clastogenicity of Croton palanostigma sap using the comet assay and micronucleus test in cells of mice submitted to acute treatment. Material and methods HPLC analysis was performed to identify the main components of the sap. The sap was administered by oral gavage at doses of 300 mg/kg, 1000 mg/kg and 2000 mg/kg. For the analysis, the comet assay was performed on the leukocytes and liver cells collected 24 h after treatment, and the micronucleus test (MN) on bone marrow cells. Cytotoxicity was assessed by scoring 200 consecutive polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE/NCE ratio). Results and conclusion The alkaloid taspine was the main compound indentified in the crude sap of Croton palanostigma. The results of the genotoxicity assessment show that all sap doses tested produced genotoxic effects in leukocytes and liver cells and also produced clastogenic/aneugenic effects in bone marrow cells of mice at the two higher doses tested. The PCE/NCE ratio indicated no cytotoxicity. The data obtained suggest caution in the use of Croton palanostigma sap by humans considering its risk of carcinogenesis. © 2013 Elsevier B.V. All rights reserved.
Keywords: Comet assay; Croton palanostigma; Dragon's blood; Euphorbiaceae; Micronucleus test; Sangre de grado; alkaloid; aneugen; clastogen; dragon blood; herbaceous agent; taspine; unclassified drug; animal experiment; bone marrow cell; carcinogenesis; comet assay; controlled study; cytotoxicity; dose response; erythrocyte; genotoxicity; high performance liquid chromatography; leukocyte; liver cell; male; medicinal plant; micronucleus test; mouse; nonhuman; Mus